Single-cell transcriptome analysis identifies MIF as a novel tumor-associated neutrophil marker for pancreatic ductal adenocarcinoma - Yan Zeng; Jiaping Yu; Yutong Chen; Juan Zhuang; Xinyue Liang; Yaning Li; Shili Chen; Wenzheng Pang; Linjuan Zeng (npj Precision Oncology)
Abstract Pancreatic cancer is a common cause of cancer mortality, and pancreatic ductal adenocarcinoma (PDAC) is the most common subtype. Tumor-associated neutrophils (TANs) have been recognized as potential therapeutic targets. In this study, we utilized bulk and single-cell RNA sequencing (scRNA‒seq) to identify seven distinct subtypes of neutrophils in PDAC. Oxidized low-density lipoprotein receptor 1 (OLR1)+ neutrophils and macrophage migration inhibitory factor (MIF)+ neutrophils were classified as TANs. The clinical relevance, dynamic transitional process, function, cell‒cell communication and transcription factor activity of neutrophil subclusters in PDAC were characterized. Furthermore, the novel MIF+ TANs were fully validated in PDAC tissues, an orthotopic pancreatic tumor model and a patient-derived xenograft (PDX) model. MIF+ TANs promote the proliferation and migration of PDAC cells through the activation of the ERK and AKT pathways and epithelial‒mesenchymal transition (EMT). This study provides insight into the potential of MIF+ TANs as therapeutic targets for PDAC patients.